Magnetic Resonance Cholangiopancreatography Evaluation of Intrahepatic Biliary Tree Variants in Nepalese Population based on Yoshida classification - Sharma, Rupesh; Acharya, Sumnima; Sharma, Alina (Med Phoenix, 2022)
Introduction The meticulously arranged hierarchical structure of the biliary tree is pivotal for liver function. This biliary tree is divided into intra and extrahepatic components. The anatomic variations of the biliary tree are notoriously common with studies reporting variations in 20% to 55% of the population in different parts of the world. This may result in misdiagnosis and serious injury to the biliary system during surgical procedures. Thus, accurate knowledge of the biliary tree is essential for the interpretation of radiological examination and presurgical planning for hepatobiliary surgery such as laparoscopic cholecystectomy and liver transplant. Magnetic Resonance Cholangiopancreatography (MRCP) is a non-invasive and safe modality for the accurate evaluation of the biliary tree. Materials and Methods It was a prospective cross-sectional study performed using a 1.5 Tesla MRI machine. The complete morphology of intrahepatic bile ducts was evaluated and categorized as per Yoshida classification and compared with past literature. Results A total of 76 patients were studied during the period out of which 24 (31.6%) were males and 52 (68.4%) were females. The normal morphology of intrahepatic ducts (Yoshida type I) was found only in 44 (57.9%) cases and the rest of the cases (42.1%) showed variant anatomy. Yoshida type II was the next most common morphology. The study also found no significant correlation between the sex of the patient and the morphological variant. Conclusion Morphological variation of intrahepatic biliary ducts is very common. MRCP is a non-invasive and reliable method for the evaluation of intrahepatic biliary anatomy and its variants.